Thermal‐Responsive Phosphorescent Nanoamplifiers Assembled from Two Metallophosphors - Sun, Meng‐Jia; Zhong, Yu‐Wu; Yao, Jiannian (Angewandte Chemie International Edition, 2018)
Thermal‐responsive phosphorescent nanotubes have been fabricated from the co‐assembly of two neutral iridium complexes, which behave as the antenna chromophores and energy acceptors, respectively, in these highly ordered crystalline superstructures. By tuning the acceptor doping ratio in a range of 0 to 0.5 %, these tubes display color‐tunable phosphorescence from green to red at room temperature, and it is attributed to the highly efficient light‐harvesting and energy transfer within these materials. For the same reason, the acceptor emission in the nanotubes is amplified more than 800 times with respect to its pure non‐emissive solid sample. The doped tubes show reversible thermal‐responsiveness, in which the energy transfer was completely suppressed at 77 K and reactivated at room temperature. These processes were characterized by the in situ emission color (green, orange, and red) and spectral changes and lifetime measurements of isolated nanotubes. The temperature‐controlled exciton dynamics are responsible for the luminescent thermochromism in these crystalline materials. With flying colors: The co‐assembly of two neutral iridium complexes gives rise to crystalline phosphorescent nanotubes with highly efficient light‐harvesting and energy‐transfer properties. They display color‐tunable and thermal‐responsive phosphorescence from green to red at a low acceptor doping ratio of less than 0.2 %. The acceptor emission in the crystalline nanotubes is amplified more than 800 times with respect to its non‐emissive pure solid sample.